2017
DOI: 10.7862/rb.2017.202
|View full text |Cite
|
Sign up to set email alerts
|

Rola Lasów I Leśnictwa W Pochłanianiu Gazów Cieplarnianych

Abstract: Wśród działań zmierzających do złagodzenia zmian klimatycznych ważną rolę odgrywają lasy oraz aktywnie prowadzona gospodarka leśna. Lasy pełnią rolę nie tylko pochłaniacza dwutlenku węgla, ale stanowią ważne źródło surowca drzewnego i biomasy leśnej, dostarczając substytutów materiałów niedrzewnych oraz paliw kopalnych. Obecnie, informacje o działaniach w zakresie zalesień, wylesień oraz gospodarki leśnej stanowią część corocznych raportów, przygotowywanych na mocy ramowej konwencji klimatycznej oraz protokołu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Forest ecosystems assimilate much carbon dioxide, especially during the development cycle. What's more, it can be said that forests are living carbon dioxide storage systems (Jabłoński & Stempski 2017). It is worth noting that further research is needed to indicate the role of old trees in CO 2 assimilation and emissions balance (however, it is indicated that old-growth forests still accumulate carbon dioxide, but the rate of the assimilation is lower) (Jaroszewicz et al 2021).…”
Section: Location Factors Relating To Photovoltaic Power Plantsmentioning
confidence: 99%
“…Forest ecosystems assimilate much carbon dioxide, especially during the development cycle. What's more, it can be said that forests are living carbon dioxide storage systems (Jabłoński & Stempski 2017). It is worth noting that further research is needed to indicate the role of old trees in CO 2 assimilation and emissions balance (however, it is indicated that old-growth forests still accumulate carbon dioxide, but the rate of the assimilation is lower) (Jaroszewicz et al 2021).…”
Section: Location Factors Relating To Photovoltaic Power Plantsmentioning
confidence: 99%
“…(December 31, 2021); or 9,464,000 ha according to the standard adopted for international assessments, taking into account land related to forest management (Zajączkowski et al, 2022). This accounts for approximately 30% of the country's total land area (Figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…The constant impact of pollutants and their previous accumulation in the forest environment increase the predisposition of forests to diseases. In 2020, the health status of forests in Poland, assessed by crown defoliation, deteriorated [11]. Data presented by Polish Forest Research Institute indicate that severe drought was the main abiotic factor weakening and damaging tree stands in Poland in years 2018-2020 practically across the entire country.…”
Section: Forest Treatmentmentioning
confidence: 99%
“…Timber harvested as part of sanitary cuts amounted in 2020 to 6.1 million m3. Most of the harvested mass was snag (4.3 million m3 -72%), of which 45% was wood actively colonized by secondary pests [11].…”
Section: Forest Treatmentmentioning
confidence: 99%